A horizontally polarized, low-profile and compact antenna for radiating parallel to ground plane - Lertsakwimarn, Kittima; Phongcharoenpanich, Chuwong; Fukusako, Takeshi (My University, 2014)
This paper presents a low-profile, horizontally polarized and compact printed antenna radiating parallel to the ground plane. The proposed antenna consists of a small inner feeding loop, a coupled split ring element and a ground plane. The dimension of the proposed antenna is 45 mm × 50.5 mm × 11.6 mm (0.138λ0 × 0.155λ0 × 0.036λ0). From the results, the -10-dB S11 of the antenna covers the 920-MHz RFID band, and the gain is about 1.45 dBi in the parallel direction to the ground plane. The measured results show a good agreement with simulated results.
Keywords: horizontal polarization; low-profile antenna; radiating parallel to ground plane